THE ROLE OF EDUCATIONAL STAFF ON IMPROVING STUDENT SERVICE QUALITY AT MTSN 1 BONDOWOSO - Fariz, Mochammad Chairul (STAI Ma'had Aly Al-Hikam Malang, 2025)
Educational staff hold a strategic role as the primary support in creating a conducive, effective, and efficient learning environment. This study aims to examine the role of educational staff in improving the quality of student services at MTsN 1 Bondowoso. This research employs a qualitative approach. The method used for data collection is the participatory observation method, in which the researcher observes the speech and service strategies of educational staff through recording and note-taking techniques, complemented by interviews. Once the data were collected, the researcher conducted data analysis, including transcription, reduction, classification, tabulation, validation, interpretation, and conclusion drawing. The results indicate that the quality of student services at MTsN 1 Bondowoso through the drumband activity involves three main stages: planning, implementation, and evaluation. The planning stage includes systematic program design, guidance by professionals, learning of music notation, recruitment based on students’ interests and potential, effective distribution of musical instruments, and structured talent development. In the implementation stage, the drumband serves as a strategy for improving service quality through Qirab Devile and Display performances, which integrate Islamic values, discipline, teamwork, and meaningful learning. Meanwhile, the evaluation highlights the strategic role of the activity in holistic education, training effectiveness, member selection and coaching, parental involvement, team coordination, and the tangible contribution of educational staff to the program’s success. Thus, the drumband activity has proven to be an effective medium for enhancing the quality of educational services and fostering comprehensive student character development.